2019
DOI: 10.1002/anie.201908805
|View full text |Cite
|
Sign up to set email alerts
|

Expedient Synthesis of Core Disaccharide Building Blocks from Natural Polysaccharides for Heparan Sulfate Oligosaccharide Assembly

Abstract: The complex sulfation motifs of heparan sulfate glycosaminoglycans (HS GAGs) play critical roles in many important biological processes. However, an understanding of their specific functions has been hampered by an inability to synthesize large numbers of diverse, yet defined, HS structures. Herein, we describe a new approach to access the four core disaccharides required for HS/heparin oligosaccharide assembly from natural polysaccharides. The use of disaccharides rather than monosaccharides as minimal precur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 56 publications
0
22
0
Order By: Relevance
“…Hsieh‐Wilson and co‐workers’ have recently described novel access to key HS disaccharide building blocks 35 a – d (Scheme 7). [23] Notably, two of the four core disaccharides generally required for HS assembly were obtained via digestion of readily available natural polysaccharides, enabling a cost‐effective and scalable entry to such materials. Firstly, heparin was hydrolysed to a crude disaccharide using 2 M TfOH at 100 °C, followed by carboxylate esterification and O/ N ‐acetylation in one pot to afford the core d ‐GlcN‐ l ‐IdoA disaccharide 35 a in 18 % yield over 4 steps.…”
Section: Synthetic Methodology Developments For Heparan Sulfate Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Hsieh‐Wilson and co‐workers’ have recently described novel access to key HS disaccharide building blocks 35 a – d (Scheme 7). [23] Notably, two of the four core disaccharides generally required for HS assembly were obtained via digestion of readily available natural polysaccharides, enabling a cost‐effective and scalable entry to such materials. Firstly, heparin was hydrolysed to a crude disaccharide using 2 M TfOH at 100 °C, followed by carboxylate esterification and O/ N ‐acetylation in one pot to afford the core d ‐GlcN‐ l ‐IdoA disaccharide 35 a in 18 % yield over 4 steps.…”
Section: Synthetic Methodology Developments For Heparan Sulfate Synthesismentioning
confidence: 99%
“…Hsieh-Wilson and co-workers' have recently described novel access to key HS disaccharide building blocks 35 a-d (Scheme 7). [23] Notably, two of the four core disaccharides generally required for HS assembly were obtained via digestion The authors were also able to access more complex, orthogonally protected disaccharide building blocks, exempli-fied by 37, in just nine steps from heparin (Scheme 8). Disaccharide 37 then underwent strategic protecting group manipulations to afford both donor 38 and acceptor 39 components.…”
Section: Hs Building Blocks From Polysaccharide Digestionmentioning
confidence: 99%
“…Recently, a clever approach suggested the controlled hydrolysis of commercially available heparin and heparosan polymers to overcome the challenges associated with the chemical synthesis of the disaccharide cores ( Scheme 20 ) [ 405 ]. NMR spectroscopy revealed that, after acid hydrolysis, both polymers produced one type of dimer as the major product (e.g., A-B or B-A).…”
Section: Reviewmentioning
confidence: 99%
“…Pawar et al. employed the C5‐bromo reduction strategy via Bu 3 SnH based epimerization reaction in disaccharides of Heparin and N−Ac‐Heparin [45] …”
Section: Strategies For the Synthesis Of L‐sugarsmentioning
confidence: 99%
“…Pawar et al employed the C5-bromo reduction strategy via Bu 3 SnH based epimerization reaction in disaccharides of Heparin and NÀ Ac-Heparin. [45] Yet another well explored C5 epimerization method for the synthesis of L-sugar starting from alkenes is through hydroboration/oxidation. The technique requires 6-deoxy D-sugar unit on which elimination is performed to get an exocyclic alkene.…”
Section: C5 Epimerization Of D-hexosesmentioning
confidence: 99%